2022
DOI: 10.1038/s41598-022-25361-5
|View full text |Cite
|
Sign up to set email alerts
|

Crash severity analysis and risk factors identification based on an alternate data source: a case study of developing country

Abstract: Road traffic injuries are one of the primary reasons for death, especially in developing countries like Bangladesh. Safety in land transport is one of the major concerns for road safety authorities and other policymakers. For this reason, contributory factors identification associated with crashes is necessary for reducing road crashes and ensuring transportation safety. This paper presents an analytical approach to identifying significant contributing factors of Bangladesh road crashes by evaluating the road … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Table 1 summarizes the results obtained from the first set of experiments, including overall mean precision, recall, F1 score, and weighted F1 score values. The approach with the highest F1 score, which is the harmonic mean of precision and recall 25 , was considered the most accurate. The weighted F1 score was also provided to evaluate the proposed methods, considering class imbalance 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the results obtained from the first set of experiments, including overall mean precision, recall, F1 score, and weighted F1 score values. The approach with the highest F1 score, which is the harmonic mean of precision and recall 25 , was considered the most accurate. The weighted F1 score was also provided to evaluate the proposed methods, considering class imbalance 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al (2014) [2], Rezapour et al (2018) [24], Ma et al (2023) [25] Road barrier [26], Russo & Savolainen (2018) [27], Molan et al (2020) [28] The following six factors have been identified as potential influential factors [29].…”
Section: Comparisonmentioning
confidence: 99%
“…These methods prove to be particularly advantageous in cases where the connection between predictor attributes and the targeted levels of injury severity remains poorly understood or exhibits a highly nonlinear relationship [18] [19]. RF, a commonly employed tree-based ensemble ML technique, has been found to be popular in different crash injury severity studies [20] [21]. In addition to RF, other techniques that are prominently used to predict crash injury severity include decision trees [19] [21], support vector machines (SVMs) [22], and XGBoost [19] [23].…”
Section: Introductionmentioning
confidence: 99%
“…RF, a commonly employed tree-based ensemble ML technique, has been found to be popular in different crash injury severity studies [20] [21]. In addition to RF, other techniques that are prominently used to predict crash injury severity include decision trees [19] [21], support vector machines (SVMs) [22], and XGBoost [19] [23]. Various studies used DL techniques to predict road crash severity [22] [24] [25].…”
Section: Introductionmentioning
confidence: 99%